1995
DOI: 10.1097/00003246-199505000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Validation and comparison of models predicting survival following intracerebral hemorrhage

Abstract: Model 1 predicts 30-day patient status as well as the more complex model 2. Model 1 provides a valid, easy-to-use means of categorizing supratentorial intracerebral hemorrhage patients in terms of their probability of survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
67
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(76 citation statements)
references
References 27 publications
5
67
1
3
Order By: Relevance
“…Prognostic models for outcome in patients with ICH most frequently include the initial hematoma size as assessed on NCCT in addition to clinical variables such as the GCS score, which have been found to be significant independent predictors of mortality in multiple studies. 13,[20][21][22] The present study demonstrated that the addition of intravenous contrast in the setting of acute ICH, usually performed to assess an underlying cause or substrate of hemorrhage, can provide useful information about the risk of hematoma expansion in acute ICH. This is in agreement with the recent study by Goldstein et al 15 Also, contrast extravasation on CTA/CECT independently predicted hospital mortality and 30-day mortality.…”
Section: Discussionmentioning
confidence: 67%
“…Prognostic models for outcome in patients with ICH most frequently include the initial hematoma size as assessed on NCCT in addition to clinical variables such as the GCS score, which have been found to be significant independent predictors of mortality in multiple studies. 13,[20][21][22] The present study demonstrated that the addition of intravenous contrast in the setting of acute ICH, usually performed to assess an underlying cause or substrate of hemorrhage, can provide useful information about the risk of hematoma expansion in acute ICH. This is in agreement with the recent study by Goldstein et al 15 Also, contrast extravasation on CTA/CECT independently predicted hospital mortality and 30-day mortality.…”
Section: Discussionmentioning
confidence: 67%
“…I ntraventricular hemorrhage (IVH) secondary to spontaneous intracerebral hemorrhage (ICH) results in death in 32% to 43% of cases [1][2][3][4][5][6][7][8] and poor functional outcome in most survivors. 5,7,[9][10][11][12][13][14][15] In severe IVH with obstruction of the third or fourth ventricle, the placement of an extraventricular drain can help lower raised intracranial pressure.…”
mentioning
confidence: 99%
“…8,20,35 Previous neurosurgical studies have also demonstrated age-dependent morbidity and mortality rates, with younger patients faring better than older patients undergoing craniotomy for intracranial bleeding. 13,35 However, current advances in imaging, rapid diagnostics, medical management of hemodynamic properties, and surgical techniques have improved patient outcomes, 36 and a further decrease in mortality associated with treatment for intracranial bleeding has been demonstrated; in 2008, postoperative mortality associated with craniotomy for evacuation of acute subdural and epidural hematoma ranged from 22% to 41%. 17,33,34 It is plausible that this overall decrease in mortality may also be reflected by improved survival among older patients.…”
mentioning
confidence: 99%